Active biopolymers in green non-conventional media: a sustainable tool for developing clean chemical processes. Issue 98 (26th October 2015) - Lozano, Pedro; Bernal, Juana M.; Nieto, Susana; Gomez, Celia; Garcia-Verdugo, Eduardo; Luis, Santiago V.
Abstract : By understanding structure–function relationships of active biopolymers ( e.g. enzymes and nucleic acids) in green non-conventional media, sustainable chemical processes may be developed. Abstract : The greenness of chemical processes turns around two main axes: the selectivity of catalytic transformations, and the separation of pure products. The transfer of the exquisite catalytic efficiency shown by enzymes in nature to chemical processes is an important challenge. By using appropriate reaction systems, the combination of biopolymers with supercritical carbon dioxide (scCO2 ) and ionic liquids (ILs) resulted in synergetic and outstanding platforms for developing (multi)catalytic green chemical processes, even under flow conditions. The stabilization of biocatalysts, together with the design of straightforward approaches for separation of pure products including the full recovery and reuse of enzymes/ILs systems, are essential elements for developing clean chemical processes. By understanding structure–function relationships of biopolymers in ILs, as well as for ILs themselves ( e.g. sponge-like ionic liquids, SLILs; supported ionic liquids-like phases, SILLPs, etc. ), several integral green chemical processes of (bio)catalytic transformation and pure product separation are pointed out ( e.g. the biocatalytic production of biodiesel in SLILs, etc. ). Other developments based on DNA/ILs systems, as pathfinder studies for further technological applications in the near future, are also considered.